Implementation of Making Monitoring Control System (MOS) Applications to Know Cylinder Repair Codes in Paper Production Areas - Muhammad Helmi Kurniawan; Muhammad Arif; Khusnul Khotimah Ayuningtiyas (Bulletin of Computer Science and Electrical Engineering, 2022)
The rapid development of information technology has had an impact on various fields of life and professions. An organization usually has various kinds of business processes that it wants to achieve. Business models can assist in evaluating current and common business models out of business process automation (BPA). PT. XXX is a manufacturing company that produces paper with the largest output in Indonesia. The company is committed to implementing sustainable business principles in all of its operational activities. So far, Control Monitoring activities at the company are still carried out manually, starting from taking samples, checking the standard of a spare part, to preparing reports. This causes the ineffectiveness of the work cycle, so to overcome these problems a computerized system is created in the form of a Monitoring Control System (MOS) application for the Finance & Accounting department. With this application program, it is hoped that it will be able to reduce the use of paper in the process of monitoring, recording, and speed up the preparation of reports so that they are more quickly received by other departments at PT XXX.